2020
DOI: 10.1002/solr.201900568
|View full text |Cite
|
Sign up to set email alerts
|

NiS‐Decorated ZnO/ZnS Nanorod Heterostructures for Enhanced Photocatalytic Hydrogen Production: Insight into the Role of NiS

Abstract: Loading cocatalysts can effectively enhance the surface hydrogen reduction in photocatalytic water splitting by introducing a positive Schottky barrier. NiS is regarded as a promising cocatalyst to replace the noble metals due to its low cost and equivalent or even better performance. However, there is a huge controversy over whether the NiS cocatalyst is used to trap electrons or holes in the photocatalytic process. Herein, a new type of NiS‐decorated ZnO/ZnS (ZnOS) nanorod heterostructure photocatalysts is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…[46] Figure 5f shows that the H 2 evolution current of NMT decreases with the slowest rate, suggesting the highest H 2 evolution overpotential. [47] In comparison, the overpotential of NMTCZ-45 S-scheme heterojunction is quickly reduced to a certain extent. The lower overpotential could be attributed to the fast transfer of photogenerated electrons and efficiently accelerated electrocatalytic H 2 evolution kinetics, resulting in enhanced PHE activity of NMTCZ-45.…”
Section: Resultsmentioning
confidence: 99%
“…[46] Figure 5f shows that the H 2 evolution current of NMT decreases with the slowest rate, suggesting the highest H 2 evolution overpotential. [47] In comparison, the overpotential of NMTCZ-45 S-scheme heterojunction is quickly reduced to a certain extent. The lower overpotential could be attributed to the fast transfer of photogenerated electrons and efficiently accelerated electrocatalytic H 2 evolution kinetics, resulting in enhanced PHE activity of NMTCZ-45.…”
Section: Resultsmentioning
confidence: 99%
“…The low‐cost NiS co‐catalyst has received attention because of its comparatively flat Fermi level and large work function (5.50 eV), which is close to that of Pt (5.65 eV) 77 . In a previous study, a ZnO/ZnS/NiS sample exhibited an improved photocatalytic H 2 evolution rate that was approximately 10, 7, and 4 times higher than ZnO, ZnO/ZnS, and Pt/ZnO/ZbS, respectively 78 . Pure NiS has no photocatalytic activity for H 2 production, indicating that NiS acts as the co‐catalyst in NiS/ZnO/ZnS photocatalyst.…”
Section: Co‐catalysts On Metal Oxides For Photocatalytic Hydrogen Gen...mentioning
confidence: 99%
“…The Mott-Schottky (MS) plots of ZnS and CeO 2 showed a positive slope, it indicated that the ZnS and CeO 2 were n-type semiconductor. [50] The flat band potential was derived from the intersection of the tangent line and the x-coordinate of the curve. [51][52] Flat band potentials of ZnS and CeO 2 were 0.3 V and 0.8 V, and they were À 0.06 V and À 0.56 V relative to the standard hydrogen electrode (NHE) band potentials.…”
Section: Photocatalytic Mechanism Of Ceo 2 /Zns-cus Compositementioning
confidence: 99%